Analisis Pengeluaran Rumah Tangga Petani Tidak Miskin dan Miskin (Studi Kasus di Desa Raimuna Kecamatan Maligano Kabupaten Muna) - Sugianto, Edi; Mukhtar, Mukhtar; Zani, Munirwan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This study aims to determine and analyze the proportion of food and non-food household expenditures of poor and non-poor farmers in Raimuna Village, Maligano Subdistrict, Muna Regency and the factors that influence food and non-food expenditure, both poor and not poor. farmers either simultaneously or partially. The population in the study of all farm households in Raimuna Village, Maligano District, Muna Regency was 226 families. Sampling in this study using the Slovin formula is Stratified Random Sampling. Based on the results of the study it can be concluded that the income factor, the number of family members has a significant/significant effect on food expenditure. while the education of the family head and dummy did not significantly influence food expenditure. For non-food income factors, the number of family members and dummy farmer groups has a significant effect on non-food expenditure. while the education of the head of the family does not significantly influence the variable non-food expenditure.